The Effect Of Capital Structure (Der) And Net Profit On The Profitability (Roe) Of Manufacturing Companies Listed On The Indonesia Stock Exchange For The Period 2020-2025 - Septya utami; Hayatul Millah; Yeni Kartikawati (Economics and Digital Business Review, 2026)
Profitability is one of the important indicators in assessing a company's financial performance. The level of profitability can be influenced by various factors, including capital structure and net profit. An imoptimal capital structure can increase a company's financial risk, while net profit reflects a company's ability to generate profits from its operational activities. Therefore, research is needed to determine the influence of capital structure and net profit on profitability in manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX). This study aims to analyze the influence of capital structure measured by Debt to Equity Ratio (DER) and net profit on profitability as measured by Return on Equity (ROE) in manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange for the period 2020–2025. The research method used is a quantitative method with an associative approach. The data used is in the form of secondary data obtained from the company's annual financial statements published through the Indonesia Stock Exchange and the company's official website. The sampling technique used purposive sampling with a sample of five companies. Data analysis was carried out using multiple linear regression analysis to test the influence of independent variables on dependent variables. The results of the study show that empirical evidence was obtained regarding the influence of capital structure and net profit on the profitability of the company. This research is expected to contribute to companies in managing capital structures effectively to increase profitability, as well as being a consideration for investors in making investment decisions.